PENGEMBANGAN PERANGKAT PENILAIAN BERBASIS KELAS PADA MATA PELAJARAN IPA BIOLOGI SMP KELAS VIII - Sri Ayuni; Arnentis Arnentis; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The aim of this reasearch was to develop assessment tools based on class for Biology Science subject on VIIIth grade public Junior High School. This study held on January until March 2014. This kind of study was Research and Development. This development is based on ADDIE models which consists of 5 phase, they are Analyze, Design, Development, Implementation and Evaluation. This subject of reasearch was KI dan KD and main materialis on VIIIth grade. This reasearch was analyzed by descriptive. Validity of assessment tools was determined by average score from validator. 3,6 for written assessment, 3,79 for behavior assessment, 3,86 for work assessment, 3,84 product assessment, 3,91 project assessment, 3,95 for self assessment, 3,95 for portofolio assessment and all were categorized in very valid. Based on result of reasearch can be concluded that validity result of assessment tools based on class for Biology science subject on VIIIth grade got very valid category and could be implemented in learning process.Keyword: Development Reasearch, Assessment Tools Based on Class, Biology Science SubjectWisuda Oktober